Clinicopathologic Spectrum of Xanthogranulomatous Pyelonephritis: A Single Center Experience over 8 Years - Farhat Abbas; Summyia Farooq; Gul Aalmeen; Muzamil Latief; Mohsin Wani (Journal of Renal and Hepatic Disorders, 2022)
Xanthogranulomatous pyelonephritis (XGP) is a chronic pyelonephritis subtype in which destruction of the renal parenchymal occurs, resulting in progressive loss of kidney functions. Although middle age is the predominant age group affected, but it can be spotted at any age. There is accumulation of macrophages (lipid-laden), leading to renal parenchymal destruction and fibrosis. In this study, we present our data of 15 patients who had undergone nephrectomy and had biopsy-proven XGP. XGP constituted 4.53% of the 331 nephrectomies performed for infective causes over a period of 8 years. All our patients had undergone unilateral total nephrectomy. Demographic and clinical data were analyzed after taking consent from all the patients. The age range of patients in our study was 18–65 years with a mean age of 43.93 ± 13.86 years. Ten (66.6%) of our patients were females. Diabetes was present in 40% of the patients. Three patients had imaging, suggestive of pyonephrosis, 3 had perinephric collection and 9 patients (60%) had concomitant nephrolithiasis. All the kidneys were grossly enlarged and were nonfunctional on renal scintigraphy. XGP is a form of chronic pyelonephritis, which, although less common, is devastating because of destruction of the renal parenchyma and associated morbidity. Clinicoradiologic correlation cannot be overemphasized. Definitive diagnosis is established through histopathologic examination.